2019
DOI: 10.1590/0001-3765201920180196
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Graduate Students at the University of São Paulo about Plagiarism Practices in Academic Works

Abstract: Our objective was to identify the understanding of theoretical aspects and the interpretation of practical situations that a sample of 3,623 graduate students (Population = 22,438) at the University of São Paulo (Brazil) have regarding academic plagiarism. The survey used an electronic questionnaire containing 30 multiple choice questions developed from the literature concerning the concept and definition of plagiarism, occurrence modality, types of plagiarism, reasons for occurrence, standards and preventive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Additionally, sanctions do not seem to be able to prevent people from being willing to plagiarize [50], and the technical training related to the correct use of research resources does not seem to be sufficient in preventing plagiarism [56].…”
Section: Building Upon Already Manifest Trends In Using the Internetmentioning
confidence: 99%
“…Additionally, sanctions do not seem to be able to prevent people from being willing to plagiarize [50], and the technical training related to the correct use of research resources does not seem to be sufficient in preventing plagiarism [56].…”
Section: Building Upon Already Manifest Trends In Using the Internetmentioning
confidence: 99%
“…In some situations, it is reported that even training courses may not necessarily produce desired results. For example, in Brazil, Krokoscz and Ferreira (2019) pointed to a gap between theoretical and practical knowledge regarding plagiarism for graduate students. They emphasized that although the technical training related to the correct use of research sources is necessary in the capacity-building process, it is not sufficient to prevent plagiarism practices.…”
Section: Literature Reviewmentioning
confidence: 99%